Influence of ledaers’ social capital on change implementation - Szarek, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article, based on empirical research in one of the production and service companies acting in energy industry, develops the introductory implications on how social capital of change leaders is linked to the effectiveness of change implementation. Using organisational network analysis the author examines influence of social capital of change leaders in the area of real work flow during change implementation and open communication flow on change effectiveness. One finds that ties among change leaders in those two dimensions have distinct change effectiveness effects. In broaden aspect, findings have major implications on change management research and imply further research in this matter to be conducted by the author
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 496, s. 171-182
Keywords: social network analysis; social capital; organisational changes; change management; społeczna analiza sieci; kapitał relacyjny; zmiany organizacyjne; zarządzanie zmianą